Tourism Labor, Embodied Suffering, and the Deportation Regime in the Dominican Republic. (8th May 2018) - Padilla, Mark; Colón‐Burgos, José Félix; Varas‐Díaz, Nelson; Matiz‐Reyes, Armando; Parker, Caroline Mary
Abstract: In this article, we use syndemic theory to examine socio‐structural factors that result in heightened vulnerability to HIV infection and drug addiction among Dominican deportees who survive post‐deportation through informal tourism labor. Through an ongoing NIDA‐funded ethnographic study of the syndemic of HIV and problematic drug use among men involved in tourism labor in the Dominican Republic, we argue that the legal and political–economic context of the global deportation regime contributes to structural vulnerabilities among deportees in the Dominican Republic, most of whom are men with histories of incarceration in the United States and/or Puerto Rico. While Dominican laws and institutional practices work conjointly with foreign policies to reconfigure non‐criminal deportees as hardened criminals unworthy of full citizenship rights, the informal tourism economy provides one of the few absorption points for male deportee labor, linking the deportation regime directly to the Caribbean tourism industry.